HAK KEBEBASAN BERPENDAPAT DAN TINDAK PIDANA MAKAR - Hufron Hufron (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2019)
Basically, the crime of treason is an act that fulfills two elements, namely the intention on one side and the beginning of the implementation on the other side. The beginning of the implementation itself refers to actions tobring down a legitimate government, kill the President or Vice President, and to separate part or all of the territory of the Republic of Indonesia. The link between the right to freedom of opinion and treason crimes is freedom ofopinion, precisely freedom of expression in public, can not be said treason as long as it meets the provisions of Article 6 of Law No. 9 of 1998 concerning Freedom of Expression in Public, namely respecting the rights andfreedoms of others; respect for generally recognized moral rules; obey the laws and provisions of the applicable laws and regulations; maintain and respect public security and order; and maintaining the integrity and unity ofthe nation, and vice versa, freedom of opinion can be said as treason if carrying objects that can jeopardize public relations intended to bring down a legitimate government, to kill the President or Vice President, and to separate part or all of the territory of the State Homeland.Keywords: treason crime, freedom of opinion.